Cell signaling and growth factors in development: from molecules to organogenesis - Unsicker, Klaus; Krieglstein, Kerstin (Wiley-VCH, 2006)
Stem cells -- Germ cells -- Implantation and placentation -- Cell movements during early vertebrate morphogenesis -- Head induction -- Anterior-posterior patterning of the hindbrain: integrating boundaries and cell segregation with segment formation and identity -- Neurogenesis in the central nervous system -- Generating cell diversity -- The molecular basis of directional cell migration -- Cell dealth in organ development -- Dorso-ventral patterning of the vertebrate central nervous system -- Novel perspectives in research on the neural crest and its derivatives -- Eye development -- Mammalian inner ear development: of mice and man -- Limb development -- Skeletal development -- Musculature and growth factors -- Skin development -- Tooth development -- Gastrointestinal tract -- Cell signaling and growth factors in lung development -- Molecular genetics of liver and pancreas development -- Molecular networks in cardiac development -- Vasculogenesis -- Inductive signaling in kidney morphogenesis -- Molecular and cellular pathways for the morphogenesis of mouse sex organs